Proselytism as Epistemic Violence: A Jewish Approach to the Ethics of Religious Persuasion. (18th June 2021) - Lebens, Samuel
Abstract: The purpose of this paper is two-fold: (1) to provide a philosophical justification for the counterintuitive attitude that Judaism seems to have towards proselytism; and (2) to extend the case so as to create a general argument, applicable to all religions, against many forms of proselytism.